Juridical Analysis of the Implementation on Project of National Agrarian Operations (PRONA) In the Regency of Blora - Wahyu Arga Kurniawan; Akhmad Khisni (Jurnal Akta, 2019)
Blora Regency is one of regencies in east end of Central Java province of the run National Agricultural Operations Program or commonly referred to PRONA. In fiscal year 2017 this amount PRONA in Blora Regency is one of the largest in Central Java province that is the number 25000 certification of land. Implementation of the National Agricultural Operations Program also involves various parties including the Government of Blora, Blora Regency Land Office and Regency Head / Head of Village related to the implementation of the National Agricultural Program's operation. Research methods which I use in this research is empirical juridical. Moreover, I also use this type of field research where the author falls directly to secure the data is valid in the field. From the results of this study concluded that the juridical implementation of the National Agricultural Program Operation in Blora with fiscal year 2017 is superbly accomplished in accordance with applicable regulations is Government Regulation No. 24 of 1997 on Land Registration and Technical Guidelines Prona.Keywords: National Operations Program; Registration of Land Mass.